2022
DOI: 10.1371/journal.pone.0275464
|View full text |Cite
|
Sign up to set email alerts
|

Wood stock in neotropical streams: Quantifying and comparing instream wood among biomes and regions

Abstract: Instream wood plays important chemical, physical and ecological functions in aquatic systems, benefiting biota directly and indirectly. However, human activities along river corridors have disrupted wood recruitment and retention, usually leading to reductions in the amount of instream wood. In the tropics, where wood is believed to be more transient, the expansion of agriculture and infrastructure might be reducing instream wood stock even more than in the better studied temperate streams. However, research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Despite that, the predominantly small size of LW in the study streams (Saraiva et al, 2022) indicates that they can be easily transported. Thus, if LW pieces are not arriving from upstream it is probably because they are being degraded along the way, as expected for small-sized instream wood (Haga et al, 2002;Lienkaemper & Swanson, 1987;Merten et al, 2013).…”
Section: Main Drivers Of Wood In Neotropical Streamsmentioning
confidence: 80%
See 4 more Smart Citations
“…Despite that, the predominantly small size of LW in the study streams (Saraiva et al, 2022) indicates that they can be easily transported. Thus, if LW pieces are not arriving from upstream it is probably because they are being degraded along the way, as expected for small-sized instream wood (Haga et al, 2002;Lienkaemper & Swanson, 1987;Merten et al, 2013).…”
Section: Main Drivers Of Wood In Neotropical Streamsmentioning
confidence: 80%
“…Paula et al (2011) found that LW abundance in Southeast Brazilian streams was similar to that in temperate secondary forested streams in Germany, and that LW volume was similar or greater than in temperate old-growth forested streams in New Zealand and Japan, respectively. Likewise, Saraiva et al (2022) reported that amounts of LW in streams in Brazilian tropical forests and savannas were similar to those in temperate biomes in the United States. Both studies suggested that the differences between tropical and temperate wood stock were more related to the distribution of wood size than the total number of pieces of instream wood.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations